Evaluation of Elaeis Guineensis extract as an alternative for control Xanthamonas Oryzae / Hallery Ali - Ali, Hallery (Faculty of Plantation and Agrotechnology, 2018)
Xanthamonas oryzae caused bacterial leaf blight and bacterial leaf streak of paddy (Oryza sativa) where production of this paddy in much of Asia constrains. In attempt to explore new antibacterial agents from natural sources of Elaeis guineensis, which abundant in Malaysia was, utilizes. The application of synthetic fungicide can harmful to environment as well as to the human population. In vitro antibacterial activity against the bacteria Xanthamonas oryzae on methanol, hexane and ethyl acetate crude of leaves, fronds, empty fruit bunch and empty fruit bunch were investigate. In this study, all extract were evaluated their antimicrobial properties based on disk diffusion method. Thus, this give specific result methanol leaf and fruit extract and ethyl acetate fresh fruit bunch extract gave moderate activity on antibacterial activity.This result revealed the potentials of Elaeis guineensis in combating against Xanthamonas oryzae. However, further studies, including identification and purification of the active compounds, will need to pursue.